Exposure to Light Elicits a Spectrum of Chemical Changes in Soil. Issue 8 (30th August 2019) - Doane, Timothy A.; Silva, Lucas C.R.; Horwath, William R.
Abstract: The significance of photochemically active solar radiation is well substantiated in Earth's air and water environments, but no broad connection has yet been ascertained between sunlight and the chemical properties of land surfaces. Since it is obvious that sunlight strikes Earth every day, an inquiry into this connection was made in a simple experiment with a diverse group of 20 soils. Light‐induced alteration of most of the major elements in soil was evident, including significant changes in dissolved organic carbon, inorganic nitrogen, pH, phosphorus availability and sorption capacity, and soluble and mineral forms of iron, manganese, aluminum, silicon, and calcium. In many instances the extent of these changes could be predicted from initial values. This broad response to light attests to the vivid photochemistry of soils and has both pedological and edaphological implications that reach beyond the surface. The phenomena reported here affirm the opportunity for novel inquiries into the chemistry of soils and land surfaces in general. Key Points: UV/visible radiation alters the forms and potential fate of major elements in soil The magnitude and direction of changes in some chemical properties depend on baseline values Light is a unique factor in the progressive development of land surfaces